No effect of habitat fragmentation on post-fledging, first-year and adult survival in the middle spotted woodpecker - Robles, Hugo; Ciudad, Carlos; Vera, Rubén; Baglione, Vittorio (Ecography, 2007)
Despite its relevance for the dynamics of populations, the ecological mechanisms underlying juvenile and adult survival are poorly known in most bird species. This study focuses on the effect of habitat fragmentation on early post-fledging, first-year and adult survival of the middle spotted woodpecker Dendrocopus medius by combining data of radio-tagged and ringed birds. Among juveniles, most deaths occurred during the first three weeks after fledging (survival rate: 0.35990.077) and were mainly caused by predation. After independence, birds faced another critical period during their first autumn-winter that lowered first-year survival further (0.25590.044), whereas adult mortality was considerably lower (annual survival rate: 0.78690.074). We did not find any significant effect of habitat fragmentation (measured as patch size and connectivity) on juvenile or adult survival. Sex ratio at fledging did not differ significantly from parity (proportion of females: 0.513) and was not correlated to patch size. Regardless of age, survival did not differ between the sexes, suggesting that a femalebiased mortality was not the mechanism behind the presence of unpaired territorial males in this population. Lighter nestlings underwent significantly higher post-fledging mortality, indicating that conditions in the nest may substantially affect survival later in life.
Keywords: Habitat fragmentation; middle spotted woodpecker; Mortality (voyant); Survival

No effect of habitat fragmentation on post-fledging, first-year and adult survival in the middle spotted woodpecker (Ecography, 2007)
Despite its relevance for the dynamics of populations, the ecological mechanisms underlying juvenile and adult survival are poorly known in most bird species. This study focuses on the effect of habitat fragmentation on early post-fledging, first-year and adult survival of the middle spotted woodpecker Dendrocopus medius by combining data of radio-tagged and ringed birds. Among juveniles, most deaths occurred during the first three weeks after fledging (survival rate: 0.35990.077) and were mainly caused by predation. After independence, birds faced another critical period during their first autumn-winter that lowered first-year survival further (0.25590.044), whereas adult mortality was considerably lower (annual survival rate: 0.78690.074). We did not find any significant effect of habitat fragmentation (measured as patch size and connectivity) on juvenile or adult survival. Sex ratio at fledging did not differ significantly from parity (proportion of females: 0.513) and was not correlated to patch size. Regardless of age, survival did not differ between the sexes, suggesting that a femalebiased mortality was not the mechanism behind the presence of unpaired territorial males in this population. Lighter nestlings underwent significantly higher post-fledging mortality, indicating that conditions in the nest may substantially affect survival later in life.